Application of Accounting Scaffolding Learning Using Fingertips to Increase Learning Result (Dinamika Pendidikan, 2017)
The research aim to improve the student learning outcomes. Accounting scaffolding using fingertips is learning with scaffolding approach based on Zone of Proximal Development concept which uses the learning strategy/support given during a learning process based on Mnemonic Akrostik and Loci technique using fingertips that is applied at the accounting learning on journal material. This research used Classroom Action Research approach which conducted in two cycles and used the qualitative descriptive research method. The results of applying the scaffolding learning accounting using the fingertips are learning runs very well, unified nature of accounting scaffolding using the fingertips helps engaging the students and they are very active, enthusiastic/motivated and reduce frustration. It is an effective learning and it improves the students’ understanding to be more independent to achieve the learning objectives; application of accounting scaffolding learning using fingertips improves learning outcomes. The improved learning at cycle I, 78,1% is a good criteria and at cycle II, 90.6% is a good criteria, and the students’ activity at cycle I, 77% is a good criteria and at cycle II, 84% is a good criteria; and student response to learning is good because it is fun and can improve comprehension.